PGM-구배 구조를 가진 배출 제어 촉매 물품 - VJUNOV ALEKSEI; SUN YIPENG (2023)
본 발명은 기재, 기재의 60 내지 100% 길이 상에 코팅된 백금족 금속을 포함하는 하부 워시코트 층, 및 기재의 60 내지 100% 길이 상에 코팅된 백금족 금속을 포함하는 상부 워시코트 층을 포함하여 당해 상부 코팅이 하부 워시코트 층의 길이의 적어도 60%를 덮도록 하는 배출 제어 촉매 물품을 제공하며, 상부 워시코트 층, 하부 워시코트 층, 또는 양쪽 워시코트 층의 적어도 일부는 백금족 금속 구배가 있게 상기 워시코트 층(들) 내에 증착된 백금족 금속을 포함하여 상기 워시코트 층의 최상위 부분의 PGM 농도가 상기 워시코트 층의 최하위 부분의 PGM 농도에 비해 적어도 2배 더 높도록 한다. The presently invention provides an emission control catalyst article comprising a substrate, a bottom washcoat layer comprising a platinum group metal coated on the 60 to 100% length of the substrate, and a top washcoat layer comprising a platinum group metal coated on the 60 to 100% length of the substrate such that the top coat covers at least 60% of the length of the bottom washcoat layer, wherein at least a portion of the top washcoat layer, the bottom washcoat layer or both washcoat layers comprises a platinum group metal deposited within the said washcoat layer(s) with a platinum group metal gradient such that the PGM concentration in a top-most portion of the said washcoat layer is at least two time higher compared to the PGM concentration in a bottom-most portion of the said washcoat layer.